The asymmetric effects of monetary policy with respect to stock market conditions in ASEAN-5 - Zare, Roohollah; Mohamed, Azali; Habibullah, Muzafar Shah; Wan Ngah, Wan Azman Saini (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
This paper examines the asymmetric effects of monetary policy on real output in Bull and Bear phases of stock market in five ASEAN economies (Malaysia, Singapore, Indonesia, the Philippines and Thailand) using the recently developed pooled mean group (PMG) technique. Estimating the models using monthly data from 1991:1 to 2010:1, the results show that monetary policy (measured by short-term interest rate) has a negative and statistically significant long-run effect on real output in bull and bear market periods while the effects are stronger in bear periods than bulls. These results are consistent with finance constraints (capital market imperfection) models which predict that monetary policy is more effective during bear periods than bulls. In the short-run, there is not any statistically significant relationship between monetary policy and real output.